2019
DOI: 10.4038/sljpsyc.v10i1.8202
|View full text |Cite
|
Sign up to set email alerts
|

“Muddling by googling” – Cyberchondria among outpatient attendees of two hospitals in Sri Lanka

Abstract: BackgroundThe internet is widely used as a source of health information, and the negative effects of this practice is well documented. Cyberchondria, the unfounded escalation of concerns about common symptoms based on review of online information has been identified as a major concern. This area has not been studied in Sri Lanka. AimsWe studied the prevalence, nature and effects of cyberchondria among outpatients in Sri Lanka. MethodsData was gathered from 300 outpatients, 150 patients each attending a governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Still, it should be noted that the CSS has been translated into Brazilian Portuguese [22] and that Indonesian version of the CSS was used in one study [23]. The CSS was also used in published studies conducted in Pakistan [24,25], India [26,27] and Sri Lanka [28]. The original English version of the CSS was administered in some of these studies [25,27], while other studies did not provide details of translations into local languages [24,26,28].…”
Section: Other Translations Of the Cyberchondria Severity Scalementioning
confidence: 99%
“…Still, it should be noted that the CSS has been translated into Brazilian Portuguese [22] and that Indonesian version of the CSS was used in one study [23]. The CSS was also used in published studies conducted in Pakistan [24,25], India [26,27] and Sri Lanka [28]. The original English version of the CSS was administered in some of these studies [25,27], while other studies did not provide details of translations into local languages [24,26,28].…”
Section: Other Translations Of the Cyberchondria Severity Scalementioning
confidence: 99%
“…Indeed, as many as 23.3% of university students reported a significant CYB (score on the CSS-33 above the 75th percentile) in a survey-based study conducted before the COVID-19 pandemic [30]. Another recent investigation reported CYB in 16.3% of 300 outpatients attending two general hospitals (this study considered the presence of any CSS factors as being indicative of CYB) [34]. Additional investigations are needed to determine the age of onset and the influence of culture or geography on CYB.…”
Section: Natural History Of Cyberchondriamentioning
confidence: 85%
“…Seven percent of participants scored positive for cyberchondria according to the CSS threshold estimated by the ROC curve analysis. Wijesinghe et al [ 53 ], in turn, focused on outpatients from two general hospitals in Sri Lanka and estimated the prevalence of distinct symptoms of cyberchondria at 16.3%. Akhtar et al [ 54 ] analyzing a group of graduates aged at least 35 years, with no chronic medical condition, found that 24.3% of respondents experienced acute symptoms of cyberchondria, while 50.0% reported moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%